2022
DOI: 10.1038/s41388-022-02420-9
|View full text |Cite
|
Sign up to set email alerts
|

Low lamin A levels enhance confined cell migration and metastatic capacity in breast cancer

Abstract: Aberrations in nuclear size and shape are commonly used to identify cancerous tissue. However, it remains unclear whether the disturbed nuclear structure directly contributes to the cancer pathology or is merely a consequence of other events occurring during tumorigenesis. Here, we show that highly invasive and proliferative breast cancer cells frequently exhibit Akt-driven lower expression of the nuclear envelope proteins lamin A/C, leading to increased nuclear deformability that permits enhanced cell migrati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(33 citation statements)
references
References 131 publications
1
32
0
Order By: Relevance
“…Subsequently, Young's modulus, as quantitative indices of cell stiffness, was reduced in lamin A/C or vimentindepleted cells (Figure 3B−D), suggesting that cell stiffness decreased and cells became soft. 19,32 Moreover, lamin A/C deficient cells were softer than vimentin deficient cells (Figure 3D), which may be because both lamin A/C and vimentin were simultaneously reduced in lamin A/C deficient cells, while lamin A/C increased in vimentin deficient cells (Figure 3A and Figure S2A in Supporting Information). In addition, we found that ectopic expression of vimentin significantly blocked the effect of lamin A/C deletion, similar to the role of re-expression of lamin A/C in endogenous lamin A/C depleted cells (Figure 3D).…”
Section: ■ Lamin A/c and Vimentin Synergistically Regulate Confinemen...mentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently, Young's modulus, as quantitative indices of cell stiffness, was reduced in lamin A/C or vimentindepleted cells (Figure 3B−D), suggesting that cell stiffness decreased and cells became soft. 19,32 Moreover, lamin A/C deficient cells were softer than vimentin deficient cells (Figure 3D), which may be because both lamin A/C and vimentin were simultaneously reduced in lamin A/C deficient cells, while lamin A/C increased in vimentin deficient cells (Figure 3A and Figure S2A in Supporting Information). In addition, we found that ectopic expression of vimentin significantly blocked the effect of lamin A/C deletion, similar to the role of re-expression of lamin A/C in endogenous lamin A/C depleted cells (Figure 3D).…”
Section: ■ Lamin A/c and Vimentin Synergistically Regulate Confinemen...mentioning
confidence: 99%
“…In vivo, invasive cancer cells need to migrate through small interstitial spaces formed by neighboring cells and the extracellular matrix. ,, To investigate the effect of physical constraints on cell migration, we developed a cell squeeze system with precisely adjustable degrees of confinement based on a six-well plate combined with controllable cell adhesion strength by chemical modifications, reconstituting the confined microenvironments in vivo . As displayed in Figure , we fabricated micropillars with precisely controlled heights based on soft photolithography to make the PDMS confinement slides.…”
Section: Confinement Induces the Reduction Of Lamin A/c Expression Pr...mentioning
confidence: 99%
See 1 more Smart Citation
“…Remarkably, nuclear morphology plays a vital role in modulating cell fate in the continuum of cancer progression (Capo-Chichi et al, 2016;Smith et al, 2018;Fischer, 2020). In particular, the loss of emerin and lamin A show aberrations in nuclear morphology, accompanied by an increased aggressiveness of cancer cells (Reis-Sobreiro et al, 2018;Bell et al, 2022). Consistent with this finding, ovarian cancers show decreased emerin and lamin A/C levels, accompanied by a progressive destabilization of the nuclear envelope (Capochichi et al, 2011).…”
Section: Role Of Aberrant Nuclear Envelope Factors In Cancersmentioning
confidence: 88%
“…In addition, It has been observed that lamin A is either upregulated or downregulated in various types of cancer [11], contributing to the deterioration of nuclear biophysics and mechanically over-softened or over-stiffened response. These deviations significantly impact cell vitality and activity during transmigration through confined spaces [12][13][14][15][16], endothelial gaps [17] and the bloodstream [18]. The significance of these physical phenomena has sparked an interest in utilizing mathematical models and simulations to better comprehend nuclear deformation during related processes.…”
Section: Introductionmentioning
confidence: 99%